Book Review of Embracing Cultural Responsivity and Social Justice: Re-shaping Professional Identity in Counselling Psychology - Ko, Gina (Canadian Journal of Counselling and Psychotherapy, 2021)
Sandra Collins’s e-book Embracing Cultural Responsivity and Social Justice: Re-Shaping Professional Identity in Counselling Psychology integrates a well-grounded conceptual model for attending to culture and social justice in counselling with applied examples that bridge theory and practice. The book is interconnected between domains, competencies, learning outcomes, and key concepts in the culturally responsive and socially just (CRSJ) counselling model, which enhances meaningfulness, relevancy, and ease of application for readers. The interactive features of the e-book design include (a) audio and video components that bring the contents to life, (b) internal links that support easy navigation between various sections of the book, and (c) links between the concepts in each chapter and detailed glossary definitions that ground the ideas in the professional literature. This e-book is unique in its multimodality and is user friendly with language that is both professional and personal.